الألفاظ العربية في السينما الماليزية: أفلام الفنان بي. رملي نموذجاً = Arabic vocabulary in cinema in Malaysian: the artist P. Ramli as example - Ali, Asem Shehadeh Saleh (Nigeria Arabic Language Village, 2018)
هذه الدراسة تبحث في المفردات العربية التي تتوافر في أفلام الفنان الماليزي المشهور بي. رملي؛ إذ إن شخصية بي. رملي في أفلامه لا تزال تأخذ مساحة واسعة في ذاكرة ووجدان الشعب الملايوي بماليزيا، وهو فنان الشعب بلا منافس، وقد كان للفنان الراحل بي. رملي إسهام كبير في نشر المفردات العربية في أفلامه، والتي أثّرت في نشر اللغة العربية بماليزيا في ضوء تقليد الناس للفنان بي. رملي ولعناوين أفلامه أحياناً التي تحمل عناوين عربية بحتة. وهذه الدراسة تسعى إلى بيان استعمال المفردات العربية في أفلام بي. رملي، وبيان دلالاتها كي نعرف مدى تأثير الأفلام في استعمال العربية لدى الماليزيين عبر المنهج الوصفي التحليلي. توصلت الدراسة إلى أن ثمة مفردات شائعة لدى الشعب الماليزي تعبّر عن اللغة العرية دون تغيير في معناها ولفظها، وأن هناك ألفاظاً تغيّر نطقها وبقي معناها، وأن الملايويين قد شغفوا حباً بالعربية بسبب أفلامه ونطقه وأدائه للألفاظ التراكيب العربية بشكل كوميدي وممتع، فضلاً عن أنها لغة العبادة والدين بماليزيا. ********************************************************* This study examines the Arabic vocabulary that is available in the films of the famous Malaysian artist. P.Ramli; The personality of P. Ramli in his films still takes a large space in the memory and soul of the Malay people in Malaysia, and he is an unrivaled folk artist. P.Ramli contributed greatly to the dissemination of Arabic vocabulary in his films, which influenced the publication of the Arabic language in Malaysia in the light of the tradition of people to the artist and occasional titles of his films with purely Arabic titles. This study seeks to demonstrate the use of Arabic vocabulary in B films and to show their significance in order to know the extent of the impact of films on the use of Arabic by Malaysians through the descriptive analytical approach. The study found that a common vocabulary among the Malaysian people express the Arabic language without any change in its meaning and pronunciation. There are words that change its pronunciation and meaning and the Malaysians have a passion for Arabic because of its films, pronunciation, and performance of the words Arabic structures in comic, fun, and religion in Malaysia.